The Phenomenology of Self-Alienation in People With High Perfectionistic Traits - Chaudhary, Aman Ullah; Reddy, Sandeep (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to explore the lived experience of self-alienation among individuals with high perfectionistic traits.Methods and Materials: A qualitative research design was employed using in-depth semi-structured interviews with 24 participants (13 females, 11 males) aged 21–39 from various regions in India. Participants were purposively sampled based on high perfectionistic tendencies, as determined through a brief screening using items adapted from the Frost Multidimensional Perfectionism Scale. Interviews focused on internal emotional processes, identity-related experiences, and interpersonal functioning. Data collection continued until theoretical saturation was achieved. All interviews were audio-recorded, transcribed verbatim, and analyzed thematically using NVivo software (Version 12) in accordance with a phenomenological approach. Open codes were systematically categorized into subthemes and overarching themes through iterative coding and peer debriefing.Findings: Four major themes were identified: (1) Disconnection From Authentic Self, characterized by emotional numbing, identity confusion, and suppression of personal desires; (2) Internalized Criticism and Unrealistic Standards, encompassing harsh self-talk, fear of failure, and obsession with flawlessness; (3) Emotional Isolation and Disconnection From Others, marked by relational avoidance, superficial connections, and loneliness; and (4) Existential Emptiness and Loss of Meaning, involving achievement void, value confusion, and lack of intrinsic purpose. Participant narratives revealed a cycle of emotional suppression and performative self-presentation that deepened their sense of alienation and inner fragmentation.Conclusion: Self-alienation is a central psychological consequence of perfectionistic self-presentation, affecting identity, emotional regulation, and social connection.